Long-term impacts of Legionnaires’ disease on health and wellbeing: rationale, study design and baseline findings of a matched cohort study (LongLEGIO) - Melina Bigler; Malina Vaucher; Manuel Wiederkehr; Sophia Brülisauer; Werner C. Albrich; Sarah Dräger; Valentin Gisler; Isabel Akers; Daniel Mäusezahl (Swiss Medical Weekly)
BACKGROUND AND STUDY AIMS: Is there a post-acute infection syndrome for Legionnaires’ disease? Legionnaires’ disease is a form of primarily community-acquired pneumonia caused by Legionella spp. bacteria. Legionnaires’ disease and other forms of bacterial community-acquired pneumonia may lead to persistent health and wellbeing impairments. It remains unclear whether these are caused by the community-acquired pneumonia-causing pathogen or the pneumonia itself. We present the rationale and design of a matched cohort study to investigate the persistent health impacts of Legionnaires’ disease and compare them with persistent manifestations of other bacterial (Legionella test-negative) community-acquired pneumonia. We also present baseline characteristics of the study cohorts.